Reading Class Through Shakespeare, Donne, and Milton - Warley, Christopher, 1969- (New York : Cambridge University Press, 2014)
"Why study Renaissance literature? Reading Class through Shakespeare, Donne, and Milton examines six canonical Renaissance works to show that reading literature also means reading class. Warley demonstrates that careful reading offers the best way to understand social relations and in doing so he offers a detailed historical argument about what class means in the seventeenth century. Drawing on a wide range of critics, from Erich Auerbach to Jacques Rancière, from Cleanth Brooks to Theodor Adorno, from Raymond Williams to Jacques Derrida, the book implicitly defends literary criticism. It reaffirms six Renaissance poems and plays, including poems by Donne, Shakespeare's Hamlet, and Milton's Paradise Lost, as the sophisticated and moving works of art that generations of readers have loved. These accessible interpretations also offer exciting new directions for the roles of art and criticism in the contemporary, post-industrial world"--
Includes bibliographical references and index.
Machine generated contents note: 1. Of the fickle inequality that is between us 2. The fickle fee-simple 3. Just Horatio 4. Ideal Donne 5. Virtuoso Donne 6. Uncouth Milton, part one 7. Uncouth Milton, part two.
Print version record.
eBooks on EBSCOhost
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Literature and society -- England -- History -- 17th century; Social classes in literature; Renaissance -- England; Criticism; Littérature et société -- Angleterre -- Histoire -- 17e siècle.; Classes sociales dans la littérature.; Renaissance -- Angleterre; Critique; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Criticism; English literature -- Early modern; Literature and society; Renaissance; Social classes in literature; England; 1500-1700; Criticism, interpretation, etc; History